# The Method

Consider the case where: N = 1 / (1-b ) (3) Then the coordinate transformation will look like: t = (t '+ x'b / c) / (1-b ), x = (bct' + x ') / (1-b ) (4) y = y' / (1-b ) z = z '/ (1-b ) 2) derive a formula of addition of velocities. A) In the beginning, we show that the method of differentiation is not suitable for the derivation of addition of velocities. We show this for example, special relativity. We will not ask all the symbols – it is done almost identically by many authors (for example, I enjoyed the book Efimov). To derive the velocity addition use the Lorentz transformations: t = (t '+ x'v / c ) / (1-v / c ), x = (vt' + x ') / (1-v / c ) (1A) I note that in ( 1A), the sign of the velocity v changes the value of the coordinates. In this case, it (the sign) determines the direction of motion of the moving inertial frame S ', with respect to stationary inertial frame S. Next take the total differentials, share and get: dx / dt = (v + dx '/ dt') / (1 + (v / c ) (dx '/ dt')) (2A) or u = (v + u ' ) / (1 + vu '/ c ) (3A) This is the desired formula. C mathematical point of view, everything seems perfect.